2020
DOI: 10.1080/09540261.2020.1772581
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary psychiatric hospitalization in Italy: critical issues in the application of the provisions of law

Abstract: Involuntary psychiatric hospitalisation in Italy raises some critical forensic issues. We analysed the sociodemographic, psychopathological, and behavioural characteristics of involuntarily hospitalised psychiatric patients, and the effectiveness of the juridical procedure of guarantee. Case files (n ¼ 2796) related to involuntary psychiatric hospitalisation (IPH) at the Office of the Tutelary Judge of the Ordinary Court of Rome (Italy) between January 2013 and May 2016 were analysed. For each case file sociod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
1
5
1
Order By: Relevance
“…There is evidence of the association between aggression and involuntary hospitalization (Abderhalden et al, 2007;Biancosino et al, 2009;Canova Mosele et al, 2018); nevertheless, dangerousness to self or others is not a legal criterion for involuntary psychiatric hospitalization in Italy. Our result of a large proportion of involuntarily hospitalized patients among those included is not unexpected, because a large study has already shown that approximately 10% of patients undergoing involuntary psychiatric hospitalization in Italy present reasons of aggression and danger (Ferracuti et al, 2021).…”
Section: Discussionsupporting
confidence: 52%
“…There is evidence of the association between aggression and involuntary hospitalization (Abderhalden et al, 2007;Biancosino et al, 2009;Canova Mosele et al, 2018); nevertheless, dangerousness to self or others is not a legal criterion for involuntary psychiatric hospitalization in Italy. Our result of a large proportion of involuntarily hospitalized patients among those included is not unexpected, because a large study has already shown that approximately 10% of patients undergoing involuntary psychiatric hospitalization in Italy present reasons of aggression and danger (Ferracuti et al, 2021).…”
Section: Discussionsupporting
confidence: 52%
“…According to the Italian jurisdiction, involuntary treatment requires that in the opinion of two different physicians the patient suffers from psychic alterations requiring immediate intervention, refuses treatment, and cannot be adequately treated in other non-hospital-based settings. Involuntary psychiatric treatment must be confirmed by the city mayor and by a judge; danger to oneself or to others is not a legal criterion in Italy (Ferracuti et al, 2020). In the study ward, a number of definite communication strategies (Biondi et al, 2021) for dealing with patients with acute mental disorders are routinely used by specifically trained staff members in order to obtain patients’ consent to treatment, when possible.…”
Section: Methodsmentioning
confidence: 99%
“…The absence of a dangerousness criterion relates to the vision of Basaglia, and it is seen as a fundamental step to break the often-made connection between mental disorders and dangerousness ( 31 ). In Italy the dangerousness criterion is not listed as a requirement for forced treatment ( 32 ). The need for treatment criterion prevails.…”
Section: Results: Two Care-control Choreographiesmentioning
confidence: 99%